The Asymptotic Laws of the Distribution of Eigenvalues for a System of Second Order Differential Equations having Turning Points at Both Ends of the Interval - Sengupta, Debasish (The Journal of the Indian Mathematical Society, 2023)
The paper deals with the asymptotic expressions for the solutions along with their first derivatives, the distribution of the eigenvalues and the normalized eigenvector for large eigenvalues corresponding to a system of second order differential equations having turning points at both ends of the interval, under certain suitable boundary conditions.